Melt Rheological Properties of Polypropylene/Clay Nanocomposites Prepared from Masterbatch: Effect of Nanoclay Loadings and Reprocessing. (June 2019) - Chafidz, A.; Ma'mun, S.; Fardhyanti, D. S.; Kustiningsih, I.; Hidayat, A.
Abstract: In the present work, polypropylene (PP) and nanoclay in the form of masterbatch were melt compounded using a co-rotating twin screw extruder to fabricate polypropylene (PP)/clay nanocomposites. PP/clay nanocomposites samples with four different nanoclay loadings (i.e. 0, 5, 10, and 15 wt%) were prepared. Additionally, to study the effect of reprocessing on the properties of the nanocomposites, the melt compounding process was carried twice/recycle (i.e. 1 st cycle and 2 nd cycle). The surface morphological of the nanocomposites and their melt rheological behavior were investigated using a Scanning Electron Microscopy (SEM) and an oscillatory rheometer, respectively. The SEM micrographs showed that the nanoclay was well distributed in the polypropylene matrix for both 1 st and 2 nd cycles. While, the dispersion state of the nanoclay (either intercalated or exfoliated) could not be observed due to the limitation of the apparatus. Additionally, the melt rheological analysis results showed that the complex viscosity, |µ*| of all nanocomposites samples (for both 1 st and 2 nd cycles) were higher than the neat PP and the |µ*| also increased with the increase of nanoclay loadings. However, the 2 nd cycle showed a slightly higher improvement of |µ*| compared to the 1 st cycle, and the improvement of |µ*| was more prominent at lower angular frequencies (e.g. 0.1, 1, 10 rad/s) than at higher ones (e.g. 100, 500 rad/s).